HUMAN RIGHTS AS A PATHWAY IN MENTAL HEALTH SETTINGS - Panday, Rishi; Srivastava, Prashant (International Journal of Research -GRANTHAALAYAH, 2017)
Mental health is an issue which touches the lives of many people worldwide. This often affects not only the person themselves but also their family and friends. The way in which society deals with mental health issues raises many human rights points for example in relation to service provision, treatment, assessment and civil detention, protection and empowerment. The simplest way of defining human rights is that they are about balancing the inalienable rights of all of us as human beings within the community regardless of differences in birth, social origin, gender, physical differences, faith and belief, ideology, nationality and so on. There can be no disagreement with the universally acclaimed truth that human dignity is the quintessence of human rights. This article shows lights on concept of human rights and to know how it is a pathway in mental health settings.